2018
DOI: 10.1038/s41598-018-27664-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrated microRNA and mRNA expression profiling reveals a complex network regulating pomegranate (Punica granatum L.) seed hardness

Abstract: The breeding of new soft-seeded pomegranate cultivars provides new products for the market and increases farmers’ incomes, yet the genetic architecture mediating seed hardness is largely unknown. Here, the seed hardness and hundred-seed weights of 26 cultivars were determined in 2 successive years. We conducted miRNA and mRNA sequencing to analyse the seeds of two varieties of Punica granatum: soft-seeded Tunisia and hard-seeded Sanbai, at 60 and 120 d after flowering. Seed hardness was strongly positively cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 75 publications
2
29
0
Order By: Relevance
“…These genes participate in several biological pathways, including cell division, cell wall biogenesis, signal transduction, transcriptional regulation, product transport and metabolism (Figure S8). The pathways related to cell division and the cell wall structure were proved to control pomegranate seed hardness (Luo et al ., ; Niu et al ., ). We also identified many transcription factor families, such as MYB (16 genes), WRKY (five genes), AP2‐like (16 genes), MYC (two genes) and NAC (nine genes), that contained different proportions of SNPs and InDels (Figure b).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…These genes participate in several biological pathways, including cell division, cell wall biogenesis, signal transduction, transcriptional regulation, product transport and metabolism (Figure S8). The pathways related to cell division and the cell wall structure were proved to control pomegranate seed hardness (Luo et al ., ; Niu et al ., ). We also identified many transcription factor families, such as MYB (16 genes), WRKY (five genes), AP2‐like (16 genes), MYC (two genes) and NAC (nine genes), that contained different proportions of SNPs and InDels (Figure b).…”
Section: Resultsmentioning
confidence: 97%
“…We also identified many transcription factor families, such as MYB (16 genes), WRKY (five genes), AP2‐like (16 genes), MYC (two genes) and NAC (nine genes), that contained different proportions of SNPs and InDels (Figure b). Most of these transcription factors have been reported to play roles in regulating the seed hardness of pomegranates (Luo et al ., ; Xue et al ., ) and hawthorns (Dai et al ., ). In the comparison between ‘Tunisia’ and ‘Sanbai’, we detected a SNP (T‐C) at the 166‐bp position of the NAC ( PgL0137670 ) transcription factor coding sequence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several conserved and novel miRNAs in pomegranate have been identified in previous studies through high-throughput small RNA sequencing [28][29][30]. Compared with the miRNAs expressed in fruit [30], a total of 28 known miRNAs identified in this study were conserved in pistil and fruit, while 67 known miRNAs were newly identified in pistil. Of the 28 conserved miRNAs, pg-miR160a-5p, pg-miR166a-3p, pg-miR167h, pg-miR168a, pg-miR159a, pg-miR171b, and pg-miR319a-3p were abundantly enriched in both pistil and fruit, which indicated their pleiotropy in pistil and fruit development.…”
Section: Newly Identified Mirnas In Pomegranatementioning
confidence: 72%
“…The study of small RNAs in pomegranate has been reported previously [28][29][30]. However, the involvement of small RNAs in pomegranate FMFs' ovule development cessation has not yet been determined.…”
Section: Introductionmentioning
confidence: 99%